THE EXPANSION AND IMPACT OF ISLAM IN WOLLO PROVINCE, ETHIOPIA - Misganaw Tadesse Melaku (Journal of Islamic Studies and Humanities, 2022)
Wollo is a centrally located province in Ethiopia where Islam made early expansion. It is  a region where the two major religions of the country, Orthodox Christianity and Islam had their base. Many of the older Monasteries, as well as mosques of the country, are found in this province. It also served as a center for Islamic religious education for centuries. The expansion of Islam towards Wolo made the province has resulted in many forms of diversity. Such optimistic aspects of religious interactions are well studied. Thus, this paper examines the expansion of Islam in Wollo and its impact in transforming the socio-political atmosphere of the province. The expansion and Impact of Islam in Wollo Province, Ethiopia